Kurangnya Pemahaman Orang Tua Mengenai Pendidikan Yang Meningkatkan Pernikahan Dini - Rahma Amanda; Mochamad Naim; Rizki Setiawan (Jurnal Ilmiah Wahana Pendidikan, 2023)
Marriage is an activity that converts something that is not lawful into lawful, provided that the marriage is carried out in a legal way. Early marriage refers to marriages carried out by boys and girls under the age of 19. This early age is an age that is very vulnerable to unstable economic conditions, mental readiness, economic readiness, and is not an ideal age for marriage. In their teens or early ages, teenagers are still very vulnerable to various things. The purpose of this study was to see how the relationship between understanding and educational level of parents to the increase in early marriage. This study uses a qualitative observational analysis method. The population in this study consisted of 5 parents who married off their teenage children as cases. The method used in this study is interviews with respondents. The results of the study show that the factors that encourage early marriage are economic factors, education, parents, and customs. The level of education can affect a person's maturity in responding to the surrounding environment and can influence the way a person thinks or responds to the knowledge that is around him. The level of education of parents also greatly influences their children not to marry early. Parents with low education tend to lack knowledge and insight about the impact of early marriage, so they tend to support their children to engage in early marriage..